The influence of Cardan rotation sequence on angular orientation data for the lower limb in the soccer kick - Lees, A.; Barton, G.; Robinson, M. (Journal of Sports Sciences, 2010)
The influence of the Cardan rotation sequence on the orientation angles for joints is well known but has not been explored for dynamic sports movements. The purpose of this study is to establish the influence of Cardan rotation sequence on the orientation angles of the ankle, knee, and hip of the support leg and pelvis during dynamic sports movements, typified by a maximal instep kick in soccer. We found that: (a) the X (flexion/extension) axis rotations provide data that are robust for any sequence used other than the YXZ sequence, although the Y (abduction/adduction) and Z (internal/external) axes rotations are variable in both shape and offset magnitude; (b) the preferred rotation sequence is either XYZ or XZY for dynamic sports movements, although for the soccer kick the XYZ rotation sequence has been widely used and so this is recommended as a standard; and (c) most uncertainties exist in the Y and Z axes and are most apparent at the beginning of the movement. Where uncertainty exists in identifying Y and Z axes orientations, the integrated angular velocity may be considered as an alternative to determine the relative changes in segment orientation.